2016
DOI: 10.1007/s00109-016-1420-5
|View full text |Cite
|
Sign up to set email alerts
|

miR-200c: a versatile watchdog in cancer progression, EMT, and drug resistance

Abstract: MicroRNAs (miRNAs) are 20-22-nucleotide small endogenous non-coding RNAs which regulate gene expression at post-transcriptional level. In the last two decades, identification of almost 2600 miRNAs in human and their potential to be modulated opened a new avenue to target almost all hallmarks of cancer. miRNAs have been classified as tumor suppressors or oncogenes depending on the phenotype they induce, the targets they modulate, and the tissue where they function. miR-200c, an illustrious tumor suppressor, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 143 publications
3
96
0
Order By: Relevance
“…In various cancers, miR-200c has been demonstrated to be an effective tumour suppressor that inhibits cancer development, proliferation, EMT, therapy resistance, and metastasis [17, 30]. Chang et al have shown that miR-200c inhibits EMT and metastasis of breast cancer cells by targeting HMGB1 [31], and Jiao et al have reported that miR-200c inhibits the metastasis of A549 cells by targeting ZEB2, an EMT regulator [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In various cancers, miR-200c has been demonstrated to be an effective tumour suppressor that inhibits cancer development, proliferation, EMT, therapy resistance, and metastasis [17, 30]. Chang et al have shown that miR-200c inhibits EMT and metastasis of breast cancer cells by targeting HMGB1 [31], and Jiao et al have reported that miR-200c inhibits the metastasis of A549 cells by targeting ZEB2, an EMT regulator [32].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that endogenous miR-200c suppresses EMT by regulating cell adhesion through targeting the E-cadherin transcriptional repressors ZEB1 and ZEB2 [15, 16]. Furthermore, miR200c has also been reported to regulate proliferation, invasion, metastasis, and chemosensitivity in various cancers [1719]. Nevertheless, it is not known whether miR-200c acts as a tumour suppressor through downregulating HMGB1 in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs as a recent focus in tumor research serve an oncogenic or tumor-suppressive role in different cancer types via various pathways (17)(18)(19). miR-200c is a member of the miR-200 family, which is located on chromosome 12p13 and is closely associated with carcinogenesis and disease progression in a wide range of cancer types (20,21). To the best of our knowledge, there have been only 4 clinical studies on miR-200c expression in NSCLC to date, producing contradictory results (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple miRNA-based drugs have been explored and have entered clinical testing [27,28] 31. Studies on this miRNA family revealed that it has versatile roles in cancer progression, drug resistance and oxidative stress [29,30].…”
Section: Introductionmentioning
confidence: 99%